Preoperative Application of Chlorhexidine to Reduce Infection with Cesarean Delivery after Labor (PRACTICAL): A Randomized Clinical Trial - DeBolt, Chelsea A.; Rao, Manasa G.; Warren, Leslie; Johnson, Shaelyn; Rekawek, Patricia; Kaplowitz, Elianna; Overbey, Jessica; Paul, Keisha; Tavella, Nicola; Monro, Johanna; Stone, Joanne; Bianco, Angela (American Journal of Perinatology, 2023)
Objective To evaluate whether use of both preoperative 2% chlorhexidine gluconate abdominal cloth and 4% chlorhexidine gluconate vaginal scrub is effective in reducing surgical site infections (SSIs) in patients undergoing cesarean delivery after labor.Study Design This is a single-center, randomized clinical trial in which patients were randomized 1:1 to receive 2% chlorhexidine gluconate cloth applied to the abdomen in addition to the application of 4% chlorhexidine gluconate vaginal scrub versus standard of care. The primary outcome was rate of SSIs, including endometritis, by 6 weeks postdelivery. The secondary outcomes were other wound complications (erythema at the operative site, skin separation, drainage, fever, hematoma, seroma) by 6 weeks postdelivery, hospital readmission for wound complications, and day of discharge after cesarean delivery.Results A total of 319 patients between September 2018 and February 2021 met eligibility criteria: 160 were randomized to the chlorhexidine gluconate abdominal cloth and vaginal scrub group and 159 were randomized to the standard of care group. The groups did not have significant differences in maternal demographic characteristics. Of the 302 (95%) individuals included in primary analysis, there was no statistically significant difference in SSI and endometritis rate by 6 weeks postdelivery (6.6% in chlorhexidine vs. 5.3% standard of care, p = 0.65). Secondary outcomes were also similar among the two groups.Conclusion The combination of preoperative 2% chlorhexidine gluconate abdominal cloth and 4% chlorhexidine gluconate vaginal scrub does not appear to reduce the risk of SSI with cesarean delivery after trial of labor when compared with standard of care.Key Points
Keywords: antibiotics; cesarean delivery; chlorhexidine; labor; surgical site infection; wound infections